THE SIGNIFICANCE OF COMPARATIVE STUDY OF THE LEXICAL AND GRAMMATICAL CHARACTERISTICS OF PROVERBS AND SUBJECTS IN ENGLISH AND UZBEK: THE SIGNIFICANCE OF COMPARATIVE STUDY OF THE LEXICAL AND GRAMMATICAL CHARACTERISTICS OF PROVERBS AND SUBJECTS IN ENGLISH AND UZBEK - Abdullayev, Almat (Журнал иностранных языков и лингвистики, 2023)
Currently, in the translation of proverbs in particular, in the study and analysis of the lexical and grammatical features of English and Uzbek proverbs special attention is paid to the following.